Discovery of Pyranoviolin A and Its Biosynthetic Gene Cluster in Aspergillus violaceofuscus - Wei, Xingxing; Chen, Lin; Tang, Jian-Wei; Matsuda, Yudai (Frontiers in Microbiology, 2020)
A new polyketide-nonribosomal peptide hybrid molecule, pyranoviolin A (1), was discovered from the genome sequenced fungus Aspergillus violaceofuscus CBS 115571, and characterized to be the first pyranonigrin analogue harboring the C-3 methoxy group. Examination of the genome sequence of the fungus identified a putative biosynthetic gene cluster of 1, which was designated as the pyv cluster. The gene deletion experiment of the polyketide synthase (PKS)-nonribosomal peptide synthetase (NRPS) hybrid gene in the cluster confirmed the involvement of the pyv cluster in the pyranoviolin A biosynthesis. Finally, a plausible biosynthetic route leading to 1 has been proposed based on the bioinformatic analysis. Our study indicates that metabolite analysis of genome sequenced microorganisms whose metabolites have been largely unexplored facilitates the discovery of new secondary metabolites along with their biosynthetic gene clusters.